The Effect Of Location, Price, And Service On The Decision To Use Car Rental Services At PT Dewa Wisata Trans Kota Bengkulu - Wandi, Dehar; Abi , Yudi Irawan; Putra , Iswidana Utama (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the service impact on customer usage decisions. The process of customers using car rental services certainly involves various considerations, taking into account various factors before making a decision to use them, including location, price, and service at PT. Dewa Wisata Trans. Therefore, Bengkulu Car Rental business owners strive to optimize how consumers become interested and become customers. The purpose of this study was to determine the influence of location, price, and service on the decision to use a car rental at PT. Dewa Wisata Trans in Bengkulu City. The data collection method in this study used observation and questionnaire techniques, with a sample of 120 respondents. The results of the study showed that the results of multiple linear regression showed Y = 0.698 + 0.306 (X1) + 0.043 (X2) + 0.627 (X3) + 0.955. This illustrates a positive regression direction, meaning there is a significant influence between the variables of location (X1), price (X2), and service (X3) on the decision to use (Y) Car Rental at PT. Dewa Wisata Trans in Bengkulu City.From the t-test results of the location variable (X1) shows t count 3.057> t table 1.658 and significance 0.003 <0.05, meaning that location (X1) has a positive and significant effect on the decision to use (Y) on Car Rental at Pt. Dewa Wisata Trans Kota Bengkulu. The results of the price test (X2) show t count 3.526> t table 1.658 and significance 0.000 <0.05, meaning that price (X2) has a positive and significant effect on the decision to use (Y) on Car Rental at Pt. Dewa Wisata Trans Kota Bengkulu. The results of the service test (X3) show t count 9.073> t table 1.658 and significance 0.005 <0.05, meaning that service (X3) has a positive and significant effect on the decision to use (Y) Car Rental at Pt. Dewa Wisata Trans Kota Bengkulu.